2019
DOI: 10.1038/s41467-018-07927-y
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 deficiency instigates cGAS-mediated inflammatory signaling and confers sensitivity to tumor necrosis factor-alpha-mediated cytotoxicity

Abstract: Loss of BRCA2 affects genome stability and is deleterious for cellular survival. Using a genome-wide genetic screen in near-haploid KBM-7 cells, we show that tumor necrosis factor-alpha (TNFα) signaling is a determinant of cell survival upon BRCA2 inactivation. Specifically, inactivation of the TNF receptor (TNFR1) or its downstream effector SAM68 rescues cell death induced by BRCA2 inactivation. BRCA2 inactivation leads to pro-inflammatory cytokine production, including TNFα, and increases sensitivity to TNFα… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 67 publications
5
85
0
1
Order By: Relevance
“…In different cancer models, it was demonstrated that BRCA2 leads to accumulation of DNA breaks, and results in activation of p53, which promotes cell cycle arrest and activation of cell death [ 58 , 59 ]. Moreover, in cancer, BRCA2 inactivation leads to pro-inflammatory cytokines production, that is a determinant for cancer cell survival [ 60 ], and several studies have investigated the expression profile of various cytokines in patients with PDAC and Nuclear Factor kB (NF-κB) activation pathways that have also been shown to be involved in pancreatic cancer development [ 61 , 62 , 63 ]. Moreover, inhibiting NF-κB and its downstream targets, lead to the inhibition of proliferation, angiogenesis, and invasion as reported in the PDAC mouse model [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In different cancer models, it was demonstrated that BRCA2 leads to accumulation of DNA breaks, and results in activation of p53, which promotes cell cycle arrest and activation of cell death [ 58 , 59 ]. Moreover, in cancer, BRCA2 inactivation leads to pro-inflammatory cytokines production, that is a determinant for cancer cell survival [ 60 ], and several studies have investigated the expression profile of various cytokines in patients with PDAC and Nuclear Factor kB (NF-κB) activation pathways that have also been shown to be involved in pancreatic cancer development [ 61 , 62 , 63 ]. Moreover, inhibiting NF-κB and its downstream targets, lead to the inhibition of proliferation, angiogenesis, and invasion as reported in the PDAC mouse model [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…BRCA2 inactivation also leads to pro-inflammatory cytokine production, including TNFα, and increases sensitivity to TNFα. Enhanced TNFα sensitivity is also present in BRCA1 or FANCD2 inactivation [166]. BRCA2 inactivation leads to cGAS-positive micronuclei and results in a cell-intrinsic interferon response (cGAS/STING-mediated interferon response), which encompasses rewired TNFα signalling and enhances TNFα sensitivity [166].…”
Section: Homologous Recombination (Hr)mentioning
confidence: 99%
“…Thus, BRCA2 may have prevented the lysosome‐mediated degradation of the STING . Another study has indicated that the deficiency of BRCA2 inflames the activation of cGAS‐STING signaling by increasing the cGAS‐positive micronuclei to support the production of type 1 IFNs and other pro‐inflammatory cytokines . Further studies are required to investigate the BRCA2‐mediated negative regulation of the STING.…”
Section: Negative Regulation Of Cgas‐sting Signaling and Its Impact Omentioning
confidence: 99%